Study on the Dissemination Effect of AIGC Generated Content on New Media Platforms - Chen, Lunqiang (International Journal of Computer Science and Information Technology, 2025)
With the rapid advancement of AIGC technology, its potential in content creation—from text to images and videos—has grown significantly. New media platforms, known for their wide reach and interactivity, offer vast opportunities for AIGC dissemination. While AIGC enhances production efficiency, meeting high content demands, its effectiveness on evolving platforms remains uncertain. Scholars remain skeptical about AI replacing human creativity. As traditional media adapt to digital platforms, AIGC emerges as a disruptive force in the public opinion arena. Optimizing its dissemination on new media is now a critical challenge.